Increased SPON1 promotes pancreatic ductal adenocarcinoma progression by enhancing IL‐6 trans‐signalling. Issue 5 (29th April 2022) - Huo, Yanmiao; Yang, Jian; Zheng, Jiahao; Xu, Dapeng; Yang, Minwei; Tao, Lingye; Yao, Hongfei; Fu, Xueliang; Yang, Jianyu; Liu, Dejun; Hua, Rong; Zhang, Junfeng; et al.
Abstract: Objectives: This study investigated the specific molecular mechanism and the roles of extracellular matrix protein Spondin 1 (SPON1) in the development of pancreatic ductal adenocarcinoma (PDAC). Materials and Methods: The expression pattern and clinical relevance of SPON1 was determined in GEO, Ren Ji and TCGA datasets, further validated by immunohistochemical staining and Kaplan‐Meier analysis. Loss and gain of function experiments were employed to investigate the cellular function of SPON1 in vitro. Gene set enrichment analysis, luciferase assay, immunofluorescence and Western blot and immunoprecipitation were applied to reveal the underlying molecular mechanisms. Subcutaneous xenograft model was used to test the role of SPON1 in tumour growth and maintenance in vivo. Results: SPON1 is significantly upregulated in PDAC tumour tissues and correlated with progression of PDAC. Loss and gain of function experiments showed that SPON1 promotes the growth and colony formation ability of pancreatic cancer cells. Combining bioinformatics assays and experimental signalling evidences, we found that SPON1 can enhance the IL‐6/JAK/STAT3 signalling. Mechanistically, SPON1 exerts its oncogenic roles in pancreatic cancer by maintaining IL‐6R trans‐signalling through stabilizing the interaction of soluble IL‐6R (sIL‐6R) and glycoprotein‐130 (gp130) in PDAC cells. Furthermore, SPON1 depletion greatly reduced the tumour burden, exerted positive effect with gemcitabine, prolonging PDAC mice overall survival. Conclusions: Our data indicate that SPON1 expression is dramatically increased in PDAC and that SPON1 promotes tumorigenicity by activating the sIL‐6R/gp130/STAT3 axis. Collectively, our current work suggests SPON1 may be a potential therapy target for PDAC patient. Abstract : Extracellular matrix protein spondin 1 is significantly upregulated in PDAC tumour cell, which exerts its oncogenic roles in pancreatic cancer by maintaining IL6R trans‐signalling through stabilizing the interaction of sIL6R and GP130 in PDAC cell, resulting in STAT3 signalling activating and tumour cell growth.